Drug-Coated Balloons for Revascularization of Infrapopliteal Arteries: A Meta-Analysis of Randomized Trials - Cassese, Salvatore; Ndrepepa, Gjin; Liistro, Francesco; Fanelli, Fabrizio; Kufner, Sebastian; Ott, Ilka; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Kastrati, Adnan; Fusaro, Massimiliano (Jacc-Cardiovascular Interventions, 2016)
Objectives The aim of this study was to perform a meta-analysis of randomized trials investigating the outcomes of patients undergoing percutaneous revascularization with drug-coated balloons (DCBs) for atherosclerotic disease of the infrapopliteal arteries. Background The role of DCBs as revascularization therapy for infrapopliteal arteries represents a matter of ongoing controversy. Methods Scientific databases were searched for randomized trials of DCB therapy for atherosclerotic disease of the infrapopliteal arteries. The primary efficacy and safety outcomes were target lesion revascularization and amputation, respectively. Secondary outcomes were death, major adverse events, Rutherford class 5 or 6, and late lumen loss. Results A total of 641 patients enrolled in 5 trials received DCBs (n = 378) or control therapy (uncoated balloons or drug-eluting stents; n = 263). Median follow-up duration was 12 months. Patients treated with DCBs had risk for target lesion revascularization (risk ratio: 0.71; 95% confidence interval [CI]: 0.47 to 1.09; p = 0.12), amputation (risk ratio: 1.01; 95% CI: 0.65 to 1.58; p = 0.95), death (risk ratio: 1.14; 95% CI: 0.71 to 1.82; p = 0.59), major adverse events (risk ratio: 0.92; 95% CI: 0.59 to 1.43; p = 0.70), and Rutherford class 5 or 6 (risk ratio: 0.87; 95% CI: 0.46 to 1.62; p = 0.65) comparable with that of patients treated with control therapy. Lesions treated with DCBs showed lower late lumen loss (weighted mean difference -0.41; 95% CI: -0.79 to -0.03; p = 0.04) compared with those treated with control therapy. Conclusions In comparison with uncoated balloons or drug-eluting stents, the treatment of infrapopliteal arteries with DCBs is associated with similar clinical outcomes and favorable angiographic efficacy at 1-year follow-up. Further studies in larger numbers of patients are still needed to definitively address the role of DCB technology in this setting. (Drug-coated balloon for revascularization of tibialpedal arteries: a meta-analysis of randomized trials; CRD42015029283)
CRIS-Team Scopus Importer:2023-03-08
Keywords: drug-coated balloon; drug-eluting stent(s); infrapopliteal artery; meta-analysis; plain angioplasty